RELIGIOUS MODERATION IN TAFSIR NUSANTARA: BALANCING SYARIAT AND HAKIKAT IN AL-QAUL AL-BAY?N BY SYEKH SULAIMAN AR-RASULI - Melisa Rezi; Zulkifli; Eka Putra Wirman; Abrar (Al-Hijr: Journal of Adulearn World, 2026)
The discourse on religious moderation in contemporary Islamic studies is generally understood within a socio-political framework or as a form of normative tolerance, thereby paying insufficient attention to the theological and spiritual foundations that sustain it. Within this landscape of previous studies, this research offers a distinctive and novel perspective by positioning religious moderation (wasathiyyah) as a conceptual integration between syariat and hakikat, constructed directly through Qur’anic exegetical narratives within the Tafsir Nusantara tradition. This study aims to examine how Syekh Sulaiman ar-Rasuli (Inyiak Canduang) formulates the concept of religious moderation through his interpretation of Juz 30 in Tafsir al-Qaul al-Bay?n f? Tafs?r al-Qur’?n, and how this construction reflects the distinctive wasathiyyah orientation of Nusantara scholars. This research employs a qualitative method using a textual study approach (library research), through a thematic analysis of eight surahs in Juz ‘Amma as the primary data source, supported by classical tafsir literature and contemporary studies on religious moderation. The findings show that religious moderation in Inyiak Canduang’s tafsir is constructed through four main dimensions: moderation in creed, worship, social life, and psycho-spiritual life. Moderation is not understood as a compromise of religious teachings, but as a balance between firmness of faith, inner sincerity, consistency in worship, social concern, and spiritual tranquility. This study contributes to strengthening the discourse on religious moderation in Indonesia by emphasizing the importance of a theological-spiritual foundation rooted in Qur’anic exegesis as the basis for fostering authentic, contextual, and sustainable religious life.